Upaya Meningkatkan Keaktifan Belajar IPS melalui Permainan Puzzle pada Siswa di MIN 7 Gunungkidul - Muh Widodo (Jurnal Pendidikan Madrasah, 2021)
This research aims to improve the activeness of students' learning on IPS subjects by using puzzle games. This research uses class action research methods conducted in two cycles, including planning, implementation, observation, and reflection activities. The subject of the recipient of the action was a student of class VI MIN 7 Gunungkidul which amounted to 16 students. Data collection techniques are carried out through observation, interviews, and analysis of documents. Qualitative descriptive data analysis techniques with success criteria to achieve active categories with a score of ≥ 54. The results showed an increase in the activeness of learning and enthusiastic students in following the learning. Students' learning activities are more communicative and enjoyable. The increase in student activeness was indicated by the student observation score of each meeting in cycles I and II with the average total score in cycle I of 41.31 being in the fairly active category increased to 60.75 being in the active category in cycle II. From the data there was an increase in the score of 19.44. The use of puzzle games can increase the active learning of students of class VI MIN 7 Gunungkidul.